Increasing belief but issue fatigue: Changes in Australian Household Climate Change Segments between 2011 and 2016. - Mark Morrison; Kevin Parton; Donald W Hine (PLoS ONE)
Using national Australian samples collected in 2011 (n = 1927) and 2016 (n = 2503), we identified six Australian household segments which we labelled Alarmed, Concerned, Cautious, Disengaged, Doubtful and Dismissive. Between the two periods, we found the proportion of households in the Alarmed and Concerned segments was stable; however there was a decrease (28% to 20%) in the proportion of households in the Doubtful and Dismissive segments and an increase (27% to 33%) in the Cautious and Disengaged segments. We found that a greater proportion of households have personally experienced climate change, and were more likely to believe in human causation and believe that there is a scientific consensus about the issue. However, there was evidence of issue fatigue. Households were less likely to report that they had thought about climate change or talked about it with their friends in 2016 relative to 2011. They were also less likely to pursue certain climate friendly behaviours or reward or punish companies for their climate behaviours. These findings suggest a need to motivate households to maintain efforts to mitigate climate change, particularly the Cautious and Disengaged households that are more amenable to changing their views about this issue.